Two new species in Cremanthodium (Asteraceae, Senecioneae) from China - Wang, Long; Ren, Chen; Yang, Qin-Er (Phytotaxa, 2018)
Based on observations on herbarium specimens and living plants, two new species in Cremanthodium (Asteraceae, Senecioneae) from China, namely C. hongshanense from northwestern Yunnan and C. maoxianense from western Sichuan, are described and illustrated.